HRO-OFDM Scheme Design and Optimization for a Hybrid RF/VLC Baseband System - Fangzhou Wu; Li Chen; Weidong Wang (IEEE Photonics Journal, 2017)
A hybrid radio frequency (RF) and visible light communication (VLC) system can provide better data rate performance and user experience, and only the hybrid RF/VLC systems that use independent RF access points (APs) and VLC APs have been currently considered. However, a hybrid design in baseband can more centrally allocate various resources. In this paper, a new hybrid RF/VLC orthogonal frequency division multiplexing (OFDM) baseband is presented. Different from conventional OFDM baseband, the new baseband combines both RF link and VLC link in the physical layer. IQ modulation is used in RF link, whereas intensity modulation and direct detection are used in VLC link. Furthermore, the proposed hybrid of radio and optical OFDM (HRO-OFDM) scheme can better combine the different features in RF and VLC link. Based on the new hybrid baseband and HRO-OFDM, we improve the conventional optimization and consider both power allocation and bandwidth allocation. Compared with some conventional designs like RF OFDM baseband design, VLC OFDM baseband design and hybrid RF/VLC design, results show that our new design can achieve better performance and adaptively allocate bandwidth in RF/VLC links under the different distances between user and the baseband.